Identification of a Novel Pathogenic Folliculin Variant in a Chinese Family With Birt–Hogg–Dubé Syndrome (Hornstein-Knickenberg Syndrome) - Dandan Zong; Dandan Zong; Dandan Zong; Jinhua Li; Jinhua Li; Jinhua Li; Xiangming Liu; Xiangming Liu; Xiangming Liu; Ting Guo; Ting Guo; Ting Guo; et al. (Frontiers in Genetics, 2020)
Birt–Hogg–Dubé syndrome (BHDS), which is also called Hornstein-Knickenberg syndrome (HKS), is a hereditary autosomal dominant disorder caused by germline mutations in the folliculin gene (FLCN, NM_144997). More pulmonary manifestations (pulmonary cysts and recurrent pneumothoraxes) but fewer skin fibrofolliculomas and renal malignancy are found in Asian BHDS patients compared with other BHDS patients. The atypical manifestation can easily lead to a missed or delayed diagnosis. Here, we report a Chinese family with BHDS that presented with primary spontaneous pneumothorax (PSP) and extensive pulmonary cysts in the absence of skin lesions or renal neoplasms. Next-generation sequencing (NGS) was used to sequence the FLCN gene, and Sanger sequencing was carried out on the samples to confirm the presence of these variants. Among the 13 family members, a novel frameshift variant of FLCN (c.912delT/p.E305KfsX18) was identified in seven individuals. This variant has not been reported before. Bioinformatics analysis showed that the novel variant might lead to a premature stop codon after 18 amino acid residues in exon 9, and this may affect the expression level of FLCN. The identification of this novel frameshift variant of FLCN not only further confirms the familial inheritance of BHDS in the proband but also expands the mutational spectrum of the FLCN gene in patients with BHDS.